2021
DOI: 10.3390/app11178237
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Vacuum Extractors of Biomedical Devices of Different Materials and Pressures on the Fetal Head during Delivery

Abstract: Operative delivery requires the use of a vacuum extractor; obstetricians can choose the appropriate vacuum extractor to make the delivery process smoother and safer. However, there is no biomechanical literature focused on the imposed effects of a vacuum extractor prepared with different materials and vacuum pressure on the fetal head during the process of delivery. Therefore, we first established and performed the finite element analytical model to explore the influences of vacuum extractors manufactured from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…These study results were similar to the trends of previous studies even though previous researchers used metallic vacuum extractors and not flexible materials for examination [11]. In addition, previous studies have shown that metal vacuum extractors (358.04-361.37 N) exert more force than non-metal ones (12.229-15.064 N) [10]. When the force of attraction is greater than 135 N, such conditions may increase the risk of sphincter injury in the mother and scalp injury in the baby [28].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These study results were similar to the trends of previous studies even though previous researchers used metallic vacuum extractors and not flexible materials for examination [11]. In addition, previous studies have shown that metal vacuum extractors (358.04-361.37 N) exert more force than non-metal ones (12.229-15.064 N) [10]. When the force of attraction is greater than 135 N, such conditions may increase the risk of sphincter injury in the mother and scalp injury in the baby [28].…”
Section: Discussionsupporting
confidence: 91%
“…In order to assess the effects of different vacuum extractor sizes, we separately used vacuum extractors to act on a flat surface, hemispherical ball, and infant head model. The infant head model was mainly based on a previous study, and a geometric appearance of infant's scalp and skull was constructed based on the anatomical model of neonatal heads [10,19]. For flat surface, hemispherical ball, and fetal head models, two layered structures were used, which were 1 mm-thick scalp and 2 mm-thick skull.…”
Section: The Simulation Geometry Modelmentioning
confidence: 99%
See 2 more Smart Citations